The Relationship between Culture and Social Capital with the Sustainability of Microfinance - Firdaus, Nur (Universitas Prasetiya Mulya, 2020)
Poverty has been the biggest problem around the world, and one of the innovative solutions offered is microfinance. Since the success story of Grameen Bank has been widely spread, many countries decided to adopt microfinance programs to alleviate poverty. Microfinance is then believed as an effective instrument that can answer the poverty challenges. Several studies have analysed the impact of microfinance on poverty reduction, but the results varied. Some support that microfinance can improve the poor, but other criticise and argue that microfinance does not play a significant role to reduce the poverty rate and even undermine the poor. This article aims to analyse factors, namely culture and social capital, that can influence the sustainability of microfinance performance. The assumption used in this article is that the success of microfinance cannot be separated from the borrowers’ background that influences their behaviours towards microfinance. The article summarised a number of studies that have discussed this issue using a qualitative approach. The findings show that culture and social capital have an impact on the sustainability of microfinance, but the impacts depend on the condition of cultures and social capital in a society. However, additional supports are needed and should not be ignored to accelerate the impact of microfinance.